Pseudopus apodus Soft Tissue Anatomy Based on Comparison of Classical Dissection and Multi-Detector Computed Tomography - María Isabel García-Real; Encarnación Fernández-Valle; Sara Jiménez; María José Ruiz-Fernández; David Castejón-Ferrer; Andrés Montesinos-Barceló; María Ardiaca-García; Nerea Moreno; Juncal González-Soriano (Animals)
Anatomy is critical for understanding the physiological and biological adaptations of living creatures. In the case of Pseudopus apodus, an anguimorph lizard belonging to the Order Squamata, it is particularly important considering the scarce previous works on the morphology of its coelomic cavity. It is interesting to consider that, over the years, using non-invasive approaches in reptiles, such as diagnostic imaging methods, is becoming popular for both scientific and clinical purposes. For the present work, we used a total of five Pseudopus apodus individuals (two males and three females); one male and one female were whole-body examined by multi-detector computed tomography (CT) and then all were dissected following a conventional anatomical protocol. The novelty and the main contribution of our multi-detector CT study is to identify structures that had never been identified before using this technique, such as the opening of the vomeronasal organ and the choanae, the tongue, the glottis, the hyoid bone, the esophagus, the stomach, the small and large intestines, the cloaca, the liver, the gallbladder, the kidneys, the ovarian follicles, the trachea, the bronchial bifurcation, the lungs, the heart, the aortic arches, the aorta, the sinus venosus, and the cranial cava veins. On the contrary, other organs like the thyroid, the pancreas, the spleen, the ureters, the urinary bladder, the oviducts, the testes, the hemipenes, the pulmonary trunk, and the pulmonary arteries were only identified in the anatomical dissection. Thus, our results demonstrate that multi-detector CT scanning is a useful tool to identify a significant number of anatomical structures in Pseudopus apodus, which is important for clinical veterinary practice related to this species or different conservation programs, among other applications.